Collaborative car pooling system - Ferreira, J.; Trigo, Paulo; Filipe, P. P. (International Journal of Social, Behavioral, Educational, Economic, Business and Industrial Engineering, 2009)
This paper describes the architecture for a collaborative Car Pooling System based on a credits mechanism to motivate the cooperation among users. Users can spend the accumulated credits on parking facilities. For this, we propose a business model to support the collaboration between a car pooling system and parking facilities. The Portuguese Lisbon’s Metropolitan area is used as application scenario.